2024
DOI: 10.1186/s40164-024-00497-4
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin ligase subunit FBXO9 inhibits V-ATPase assembly and impedes lung cancer metastasis

Liang Liu,
Xiaodong Chen,
Leilei Wu
et al.

Abstract: Background The evolutionarily conserved protein FBXO9 acts as a substrate receptor for the SKP1-cullin-1-RBX1 ubiquitin ligase and is implicated in cancer, exhibiting either tumor-suppressive or oncogenic effects depending on the specific tumor type. However, their role in lung cancer metastasis remains unclear. Methods Lentiviral vectors carrying miRNA-based shRNA sequences for gene-specific knockdown were generated, and Lenti-CRISPR-Cas9 vectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It has been found that FBXO9 affects the metastasis of lung cancer cells by participating in the assembly process of the Vacuolar-type H + -ATPase (V-ATPase), thus influencing the prognosis of lung cancer patients. ( Liu et al, 2024 ). Therefore, it is critical to utilize genomic-level research in the clinical practice of cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that FBXO9 affects the metastasis of lung cancer cells by participating in the assembly process of the Vacuolar-type H + -ATPase (V-ATPase), thus influencing the prognosis of lung cancer patients. ( Liu et al, 2024 ). Therefore, it is critical to utilize genomic-level research in the clinical practice of cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that FBXO9 affects the metastasis of lung cancer cells by participating in the assembly process of the Vacuolar-type H + -ATPase (V-ATPase), thus influencing the prognosis of lung cancer patients. (Liu et al, 2024). Therefore, it is critical to utilize genomic-level research in the clinical practice of cancer treatment.…”
Section: Discussionmentioning
confidence: 99%